Grazing and feedlot performance of heifers spayed by two methods - S.B. Laudert; Gerry L. Kuhl; A.J. Edwards (Kansas Agricultural Experiment Station Research Reports, 1987)
Two field trials were conducted to compare the pasture and finishing performance of heifers spayed by the Kimberling-Rupp(K-R) technique or by flank spaying plus autografting a piece of ovarian tissue into the rumen wall (FS+A). In trial 1, neither spaying method resulted in gains of grazing heifers different from that of intake controls; however, FS+A heifers gained 5.1% faster than K-R spayed heifers. In trial 2, grazing gains of heifers spayed by the two techniques were similar. During the finishing phase, no performance difference was found among intact, K-R, or FS+A heifers in trial 1 or between K-R and FS+A heifers in trial 2.
Keywords: Cattlemen' s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Performance; Heifers; Spayed